Предмет: Алгебра, автор: ABC1234567

решите уравнение:
( x^{2} - 2x - 8)( x^{2} - 8x + 7) = 63

Ответы

Автор ответа: Artem112
0
(x^2-2x-8)(x^2-8x+7)=63
\
(x-4)(x+2)(x-7)(x-1)=63
\
(x-4)(x-1)(x+2)(x-7)=63
\
(x^2-5x+4)(x^2-5x-14)=63
\
x^2-5x=a
\
(a+4)(a-14)=63
\
a^2-10a-56=63
\
a^2-10a-119=0
\
D_1=25+119=144
\
a_1= 5+12=17
\
a_2=5-12=-7
x^2-5x=17
\
x^2-5x-17=0
\
D=25+68=93
\
x= frac{5pm sqrt{93} }{2} 
\
x^2-5x=-7
\
x^2-5x+7=0
\
D=25-28<0
Ответ:  cfrac{5pm sqrt{93} }{2}
Похожие вопросы
Предмет: Математика, автор: Lizza7272
Предмет: Биология, автор: Аноним